2017
DOI: 10.1017/s0144686x17000794
|View full text |Cite
|
Sign up to set email alerts
|

Re-thinking social exclusion in later life: a case for a new framework for measurement

Abstract: Social exclusion is a dynamic multi-dimensional process that is interactive in nature. The complex interplay between domains, whereby each domain can act as a determinant, indicator and/or outcome of social exclusion, hinders understanding of the process and the mechanisms through which social exclusion exists. This article highlights the need to disentangle these pathways and move beyond descriptive accounts of social exclusion, presenting a new working framework that allows direct hypothesis testing of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 25 publications
0
45
1
1
Order By: Relevance
“…Higher levels of education could perhaps help older people to reduce psychological stress and relieve the feeling of exclusion (Ross & Zhang, ). Data from Australia also suggest that higher education is an important protective factor from social exclusion for older people (Miranti & Yu, ). “Empty nest” older people, whose children have left home, were more likely to be excluded from social relationships and activities but they were less likely to be excluded from financial products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of education could perhaps help older people to reduce psychological stress and relieve the feeling of exclusion (Ross & Zhang, ). Data from Australia also suggest that higher education is an important protective factor from social exclusion for older people (Miranti & Yu, ). “Empty nest” older people, whose children have left home, were more likely to be excluded from social relationships and activities but they were less likely to be excluded from financial products.…”
Section: Discussionmentioning
confidence: 99%
“…Walsh et al. (, p. 81) summarised that social exclusion among older people reflects “the combination of demographic ageing patterns, on‐going economic instability and the susceptibility of ageing cohorts to increasing inequalities.” A theoretical framework to explain the factors that may lead to social exclusion of older people includes at least four perspectives: age‐related characteristics (including loss of paid work, low income and poor health – frailty or prevalence of illness due to ageing); cumulative disadvantage (vulnerable social position over the life course that leads to inequalities being more pronounced in later life compared with earlier life); ageism; and inadequate infrastructure and planning of living environments (Jose & Cherayi, ; MacLeod et al, ; Phillips & Feng, , 2018; Van Regenmortel et al., ; Yuan & Ngai, ). All of these features may limit social contact or participation of older adults in various domains of life, which results in older people being more vulnerable to social exclusion than younger age groups (Feng, ; Scharf & Keating, ; Tong & Lai, ).…”
Section: Introductionmentioning
confidence: 99%
“…Домен друштвене партиципације операционализовали су посредством укључености старих у активности организовања, волонтирања и учешћа у културним, спортским или рекреативним активностима. Последњи домен, пак, односио се на живот у самачком домаћинству, контакте се децом, присуство или одсуство партнера и пријатеља, као и изласке у друштво и посете пријатељима (MacLeod, Ross, Sacker, Netuveli, Windle, 2019).…”
Section: увод -истраживања социјалног укључивања старијихunclassified
“…The domain of social participation was operationalized through the involvement of the elderly in organizing, volunteering and participating in cultural, sporting or recreational activities. Th e last domain, however, concerned living in a single household, contacts with children, the presence or absence of partners and friends, and going out to social events and visiting friends (MacLeod, Ross, Sacker, Netuveli, Windle, 2019).…”
Section: Introduction -Research On Social Inclusion Of the Elderlymentioning
confidence: 99%
“…According to results from the English Longitudinal Study of Aging (ELSA), social exclusion can occur in multiple areas of social life, such as relationships, social activities, and cultural activities (Barnes et al, 2006). Additionally, although declines in health can be a risk factor for social exclusion, social exclusion has also been found to contribute to declines in physical health for older adults (Sacker, Ross, MacLeod, Netuveli, & Windle, 2017;Macleod, Ross, Sacker, Netuveli, & Windle, 2019). Moreover, in addition to declines in physical health, results from the ELSA revealed that social exclusion can also impact seniors' quality of life and well-being (Barnes et al, 2006).…”
Section: Social Exclusion and Social Isolationmentioning
confidence: 99%